1999
DOI: 10.1002/1529-0131(199901)42:1<90::aid-anr12>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of collagen-induced arthritis and suppression of interferon-?, interleukin-12, and tumor necrosis factor ? production by interferon-? gene therapy

Abstract: Objective. To investigate the therapeutic effects and possible mechanisms of action of constitutive expression of interferon-␤ (IFN␤) by syngeneic fibroblasts from DBA/1 mice in the collagen-induced arthritis (CIA) model.Methods. Immortalized embryonic DBA/1 fibroblasts were infected with a retrovirus expressing murine IFN␤. IFN␤-expressing fibroblasts were then implanted intraperitoneally into mice immunized with bovine type II collagen. The effect of IFN␤ on paw swelling, anticollagen antibody levels, IgG1/I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
67
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(82 citation statements)
references
References 35 publications
10
67
2
Order By: Relevance
“…The conditionally immortalized fibroblasts were derived from embryonic fibroblasts of the DBA/1 mouse by infection with a retrovirus expressing a temperaturesensitive SV40 large T antigen (52). They possess high mitotic activity when cultured in vitro at 37°C, thus enabling their propagation and transduction with genes in retroviral vectors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditionally immortalized fibroblasts were derived from embryonic fibroblasts of the DBA/1 mouse by infection with a retrovirus expressing a temperaturesensitive SV40 large T antigen (52). They possess high mitotic activity when cultured in vitro at 37°C, thus enabling their propagation and transduction with genes in retroviral vectors.…”
Section: Resultsmentioning
confidence: 99%
“…To generate immortalized DBA/1 fibroblasts, 10-12-day-old mouse DBA/1 embryos were treated with collagenase and pronase and fibroblast cell lines were grown in culture in DMEM with 10% FBS. The cells were transduced with the ecotropic retrovirus containing the large T antigen gene of SV40 tsTA58 and selected in 1 mg/ml G418 at 33°C (52).…”
Section: Methodsmentioning
confidence: 99%
“…[49][50][51] The continuous production of IFN-b by injection of IFN-b-expressing fibroblast or daily subcutaneous treatment with recombinant IFN-b inhibited inflammation as well as bone destruction in a system of collagen-induced arthritis in mice. 52,53 In addition, the expression of IFN-b was increased in synovial tissue of patients with RA. Its increased production in RA may be a reactive attempt to inhibit inflammation and bone destruction.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of sTNFR:Fc on the level of IL-12 also suggests that sTNFR:Fc may downregulate Th1 activity, since IL-12 is known to play a pivotal role in promoting the differentiation of Th1 responses and inducing IFNg production. 37 Randomized, double-blind, placebo-controlled trials showed that human p75 sTNFR:Fc fusion protein treatment yielded significant clinical benefits, with minimal toxicity, in patients with RA who had inadequate responses to other disease-modifying drugs. 17 Soluble cytokine receptors may have a distinct advantage over other TNF-neutralizing agents, such as monoclonal antibodies, in terms of immunogenicity.…”
Section: Discussionmentioning
confidence: 99%